On the Routes of Contemporary Art. - Antoniou, Klitsa (My University, 2026)
Exhibit Gallery, Barbican, London 2010 Tempus Arti: Klitsa Antoniou, Klitsa Antoniou, On the Routes of Contemporary Art. Text: Andrea Costantinou, Cyprus 2009